Strategi Pemasaran UMKM di Era Digital: Studi Kasus Gamis Hijab Terbaru Riskirich Menggunakan Aplikasi TikTok Shop - Susanti, Susanti; Vidiati, Cory (Green Publisher Indonesia, 2024)
This article discusses the digital marketing strategy used by Riskirich, an MSME operating in the Muslim fashion industry, especially robes and hijabs. The main focus of this research is the use of TikTok Shop as the main marketing and sales platform. This study aims to analyze the effectiveness of TikTok Shop in increasing brand recognition and product sales, as well as identifying the challenges and opportunities faced by Riskirich's newest hijab gamis in developing its digital marketing strategy. MSMEs in Indonesia face many challenges in marketing the products they sell, due to the COVID pandemic – 19 which occurred in 2019 to 2021 changed everything to become completely digital, so that all MSMEs in Indonesia inevitably had to market their products online. This research uses a qualitative approach with a case study method and data collection through interviews, observation and social media analysis. The research results show that using TikTok Shop significantly increases product visibility and interaction with customers, but there are challenges in terms of content management and adaptation to the platform's algorithms.